2018
DOI: 10.31223/osf.io/p5tsq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imbalance in the modern hydrologic budget of topographic catchments along the western slope of the Andes (21–25 S)

Abstract: Rates of water discharge often exceed groundwater recharge in arid catchments. This apparent mass imbalance within a catchment may be reconciled through either regional-scale groundwater flow between topographic drainages and/or the draining of stored groundwater recharged during pluvial periods. We investigate discrepancies in the modern hydrologic budget of catchments along the west flank of the Andes in northern Chile (21–25° S), focused on the endorheic Salar de Atacama basin, and adjacent basins. Our new,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 64 publications
(164 reference statements)
1
10
0
Order By: Relevance
“…The eastern margin of the basin contains several subwatersheds delineated by a 60 km long N-S oriented trough in the south called the Monturaqui-Negrillar-Tilopozo (MNT); the Miscanti fault and fold system to the east separates the basin from the Andes and controls the development of the intra-arc lakes Miñiques and Miscanti, and the broad Tumisa volcano divides the northeast from the southeast subwatersheds (Aron et al, 2008;Rissmann et al, 2015;Figures 1 and S1). A large Paleozoic structural block (Peine/Cas block), bounded by the N-S trending Toloncha fault and fold system and Peine fault is interposed in the center of the southeastern slope forming a major hydrogeologic obstruction that diverts, restricts, and focuses groundwater flow through this zone (Aron et al, 2008;Boutt et al, 2018;Breitkreuz, 1995;González et al, 2009;Jordan et al, 2002;Reutter et al, 2006; Figure 2). The N-S fold and thrust belt architecture of the basin slope forms several fault systems of varying extent and depth parallel to the salar margin; these and associated lower order faults are thought to be major conduits for groundwater flow to the surface as evidenced by the spring complexes emerging along or in the vicinity of these zones (Jordan et al, 2002).…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The eastern margin of the basin contains several subwatersheds delineated by a 60 km long N-S oriented trough in the south called the Monturaqui-Negrillar-Tilopozo (MNT); the Miscanti fault and fold system to the east separates the basin from the Andes and controls the development of the intra-arc lakes Miñiques and Miscanti, and the broad Tumisa volcano divides the northeast from the southeast subwatersheds (Aron et al, 2008;Rissmann et al, 2015;Figures 1 and S1). A large Paleozoic structural block (Peine/Cas block), bounded by the N-S trending Toloncha fault and fold system and Peine fault is interposed in the center of the southeastern slope forming a major hydrogeologic obstruction that diverts, restricts, and focuses groundwater flow through this zone (Aron et al, 2008;Boutt et al, 2018;Breitkreuz, 1995;González et al, 2009;Jordan et al, 2002;Reutter et al, 2006; Figure 2). The N-S fold and thrust belt architecture of the basin slope forms several fault systems of varying extent and depth parallel to the salar margin; these and associated lower order faults are thought to be major conduits for groundwater flow to the surface as evidenced by the spring complexes emerging along or in the vicinity of these zones (Jordan et al, 2002).…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
“…The most prominent feature in the region, the Salar de Atacama basin, is defined by very large elevation and precipitation gradients, which have led to the development of an orogenic-scale groundwater system encompassing portions of the adjacent Altiplano-Puna plateau. Recent work has concluded that solute and water influxes to Salar de Atacama would need to be 9-20 times greater than modern to account for the massive evaporite deposit accumulated there since the Miocene (Boutt et al, 2018;Corenthal et al, 2016) but also that it is possible to accumulate the Li deposit from lowtemperature weathering within a reasonable timeframe (Munk et al, 2018). Fundamental aspects of subsurface fluid flow remain unresolved including (i) catchment-wide response times to changes in recharge and water tables, (ii) spatial and temporal connections between the modern and paleohydrological systems, and (iii) the sources of additional water and solutes required to balance mass at various scales.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the previous water balances used to interpret the SdA system must be reconsidered. Previous work by Corenthal et al (2016) and Munk et al (2018) indicates that there is an imbalance between modern water and solutes delivered to the salar demonstrating that water in the basin is not sourced only from the immediate watershed but that sources of water from adjacent watersheds to the north, east and south are required to close the water balance. In summary, those works point to three exceptionally important facts about how the salar and marginal salar systems work: 1) additional water and solutes outside the topographic watershed is needed to explain the mass of the voluminous halite deposit, 2) the lagoons that exist on the margin of the salar have persisted for millions of years and have their water sourced primarily from long (old) flow paths as well as pulsed recharge from modern precipitation events, and 3) the lagoons and other freshwater sourced features that are persistent, such as springs, marshes, and lagoons are highly compartmentalized and are disconnected hydrogeologically from the massive halite nucleus (core of the salt flat) and its brine, but they rely on recharge waters from upstream aquifers in the basin.…”
Section: Introductionmentioning
confidence: 98%
“…A new conceptual model of the zones of the upper fresh/brackish regime and the lower brine regime are developed based on the hydrogeochemistry, subsurface geology, and hydraulic properties. Munk et al (2018) defined that 21% of the water flux in the entire SdA basin discharges to the southern transition zone and lagoon systems. The entire basin contributes 3.11 m 3 /s to all of the lagoon systems in SdA including the south and east lagoons (Munk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation